ANALISA DISTRIBUSI TEGANGAN TOTAL, TEGANGAN GESER MAKSIMUM DAN DEFORMASI TOTAL PADA POROS DAN ROLLBENDINGDENGAN METODE ELEMEN HINGGA MENGGUNAKAN SOFTWARE SIMULASI NUMERIC - Herri Darsan; Zulfadli (J-Innovation, 2016)
Shaft and roll bending is an element of a machine used for rolling pipes, bending pipes to curved and formed the desired angle. Roll operations often accept the burden that intersect between the pipes and the roll. The load will result in stress and strain. To make roll work safely, the various stresses and strains that occur must be calculated by using numerical simulation software to determine stresses and strains that occur on the shaft and roll bending. The bending of the shaft caused by a given load on the axis is F = 3382.339 N, and the loading on the roll bending that occurs on the surface of the exposed pipes is equal to F = 3361.51 N. Distribution of maximum shear stress that occurs in the shaft mounted roll bending is = 135.3 MPa. The maximum shear stress distribution that occurs in roll bending is = 69.91 MPa. The maximum strain distribution that occurs in roll bending is max = 9.088 x10-3 Mpa, and the maximum strain distributionthat occurs in the shaft is  max = 2.507 x10-3 Mpa. With these results, shaft and roll bending can work safelybecause the voltage that occurs does not exceed the voltage that occurs on the shaft and roll.